COMPUTATION OF AMPLIFICATION FACTOR OF THE MECHANICAL POWER AMPLIFIER FOR DIFFERENT ROPE MATERIALS (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Engineering applications often need to control a substantial output load using a relatively low control force. Mechanical power amplifiers come into play to address this requirement, providing rapid response and efficient power transfer. In this study, we focus on computing the amplification factor of a mechanical power amplifier for various rope materials, including leather, woven cotton, and steel. The experimental analysis involves a capstan mechanism, where a rope is wound around a motor-driven drum. The drum continuously rotates, but torque transmission occurs only when the input shaft constricts the drum. Our investigation aims to determine the amplification factor for different rope types. The results reveal that leather contact is optimal when the number of turns is approximately two, yielding an amplification factor of 2.23. Woven cotton contact achieves an amplification factor of 1.867. while steel contact provides an amplification factor of 1.32. Interestingly, leather outperforms woven cotton and steel in terms of power amplification. These findings align well with experimental measurements and demonstrate the mechanical power amplifier's favorable performance.